2001
DOI: 10.1007/s004200000202
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic fibres in the lung tissue of Hungarian and German lung cancer patients

Abstract: In comparison with reference values obtained by the same method for German patients with no indication of workplace asbestos exposure, increased concentrations of more than 0.2 million chrysotile fibres/g dry were obtained for six of the 25 Hungarian patients (24%). For one of them, the second highest estimate of a workplace exposure of 60 fibre-years and the highest tissue concentration of 7.38 million chrysotile fibres/g dry substantiate a high probability of a causal relationship to asbestos. A further comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 4 publications
2
7
0
2
Order By: Relevance
“…26 Our study showed similar results where 2.9% of the subjects in Central and Eastern Europe had been exposed to amphibole fibres and chrysotile, 5.2% to only chrysotile and 3.3% to unknown type of asbestos.…”
Section: Discussionsupporting
confidence: 84%
“…26 Our study showed similar results where 2.9% of the subjects in Central and Eastern Europe had been exposed to amphibole fibres and chrysotile, 5.2% to only chrysotile and 3.3% to unknown type of asbestos.…”
Section: Discussionsupporting
confidence: 84%
“…The comparison of the results from occupational history and lung tissue ®bre analysis will be published in detail elsewhere [17]. Its main points may be summarized as follows:…”
Section: Resultsmentioning
confidence: 99%
“…They were analysed by counting the ferruginous bodies (FB) with optical microscopy and by ®bre analysis with scanning transmission electron microscopy (STEM) in the Giessen Institute [17]. The method has been published earlier [15,16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moulin et al (1988), reporting on an urban population in Belgium, determined an index of 10% of AB with chrysotile cores in exposed workers, but only 3% in the general population. Finally, Rödelsperger et al (2001) found other materials, distinct from asbestos, as constituents of the cores of FB in groups of Germans and Hungarians.…”
Section: Research Articlementioning
confidence: 97%